2002
DOI: 10.1038/nm0202-150
|View full text |Cite
|
Sign up to set email alerts
|

Primary intestinal epithelial cells selectively transfer R5 HIV-1 to CCR5+ cells

Abstract: The upper gastrointestinal tract is a principal route of HIV-1 entry in vertical transmission and after oral-genital contact. The phenotype of the newly acquired virus is predominantly R5 (CCR5-tropic) and not X4 (CXCR4-tropic), although both R5 and X4 viruses are frequently inoculated onto the mucosa. Here we show that primary intestinal (jejunal) epithelial cells express galactosylceramide, an alternative primary receptor for HIV-1, and CCR5 but not CXCR4. Moreover, we show that intestinal epithelial cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
180
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(193 citation statements)
references
References 43 publications
5
180
1
7
Order By: Relevance
“…Although there is no direct evidence that LCs are the initial cells infected with HIV in humans, genetic data generated in large cohorts make it clear that CCR5 genotype is a major determinant for initial HIV susceptibility (16)(17)(18)(19). Whether CCR5 influences initial infection at the level of the LCs, at the level of the epithelial cell (43,44), at early replication steps in lymphoid tissue, or at multiple sites, however, is less clear. The former theories can be described as primary gatekeeper models, whereas the latter process represents a viral fitness model (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct evidence that LCs are the initial cells infected with HIV in humans, genetic data generated in large cohorts make it clear that CCR5 genotype is a major determinant for initial HIV susceptibility (16)(17)(18)(19). Whether CCR5 influences initial infection at the level of the LCs, at the level of the epithelial cell (43,44), at early replication steps in lymphoid tissue, or at multiple sites, however, is less clear. The former theories can be described as primary gatekeeper models, whereas the latter process represents a viral fitness model (40).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was shown that the region surrounding this epitope (corresponding to the P1 peptide, Fig. 1) mediates viral interaction with the epithelial cell receptor of HIV-1, GalCer (7,10,11). This interaction may be important for the nonfusion processes that enable HIV-1 to cross simple epithelia and can be blocked by the 2F5 IgG, ELDKWA-specific IgA from infected or highly exposed persistently seronegative individuals (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]. In addition to direct targeting of HIV-1 by neutralizing Abs (15), HIV-1 transcytosis can be blocked by disruption of rafts and by Abs against the ELDKWA epitope (7,8,10,11).…”
mentioning
confidence: 99%
“…Eine HIV-2-Infektion schützt nicht vor einer Infektion mit HIV-1 und umgekehrt [160]. Inwieweit Mutationen (Δ32-Deletion, Mutationen) im CCR5-Gen eine parenterale Infektion behindern, bleibt weiterhin fraglich [61,161]. In Deutschland trägt etwa 1 % der Bevölkerung diese Mutation, somit ist sie infektionsepidemiologisch irrelevant.…”
Section: Prävalenz Und Inzidenz Von Blutassoziierten Hiv-infektionen unclassified